Awareness of DCD from the perspective of stakeholders in the Dutch school system: a qualitative study - van Abswoude, Femke; Bakker, Meike; Hanegraaf, Linda; Bekhuis, Hidde (Frontiers in Human Neuroscience, 2025)
IntroductionDevelopmental Coordination Disorder (DCD) is one of the most prevalent developmental disorders, but largely unknown by educational professionals. The overall aim of this study was to explore awareness of DCD and ways to improve this among stakeholders in the Dutch primary school system.MethodsOne semi-structured interviews were performed with teachers (including classroom teachers (N = 8) and physical education (PE) teachers (N = 2) at primary schools), students [from teachers’ college for primary education and/or physical education (N = 7)], and other stakeholders in the primary school organization [including school organization directors (N = 2) and special needs coordinators (N = 2)]. Thematic analysis was conducted.ResultsOverall, 28.6% of the participants were aware of DCD, with percentages varying largely between participants from the school organization (100%), college students (14.3%), and teachers (10%). All participants endorsed the importance of raising awareness of DCD within the school system. It was recognized that participants can provide social support for children with DCD by stimulating both personal and social resources. All participants were open to ways to improve awareness, the responsibility of which is mostly ascribed to special need coordinators within schools.Discussion and conclusionThe results highlight both the lack of awareness of DCD among stakeholders in the primary school system in the Netherlands, as well as the importance of changing this. When teachers are aware of DCD, they can provide social support to the child which is essential to diminish the possible physical and psychological consequences. Increasing awareness within the Dutch school system may lead to better understanding, earlier diagnosis and earlier interventions for children with DCD.